Bulk nanocrystalline gamma magnesium hydride with low dehydrogenation temperature stabilized by plastic straining via high-pressure torsion. (December 2018) - Edalati, Kaveh; Kitabayashi, Kouki; Ikeda, Yuji; Matsuda, Junko; Li, Hai-Wen; Tanaka, Isao; Akiba, Etsuo; Horita, Zenji
Abstract: MgH2 with the α tetragonal structure was plastically strained using the high-pressure torsion (HPT) method and fully transformed to a nanonocrystalline γ orthorhombic phase with increasing the strain. The formation of nanocrystalline high-pressure γ phase resulted in decreasing the dehydrogenation temperature by 80 K. First-principles phonon calculations showed that both α and γ phases are dynamically stable, but the γ phase with the ionic binding has weaker hydrogen binding energy and accordingly lower dehydrogenation temperature. This study confirms the significance of crystal structure on thermal stability of hydrides for hydrogen storage applications. Graphical abstract: Unlabelled Image